Association of single-nucleotide polymorphisms in toll-like receptor 2 gene with asthma susceptibility: A meta-analysis. Issue 20 (May 2017) - Gao, Yifeng; Xiao, Hanyan; Wang, Yongbo; Xu, Feng
Abstract: Background: An increasing number of studies have been carried out on the relationship between polymorphisms in toll-like receptor 2 ( TLR2 ) gene and asthma risk. However, the results were controversial. With the purpose of yielding a more reliable estimation of the association, we conducted the present meta-analysis. Methods: Multiple electronic databases up to August 22, 2016 were searched for literature retrieval. The association between the asthma susceptibility and the rs5743708 polymorphism, rs3804099 polymorphism, rs3804100 polymorphism, and rs4696480 polymorphism in TLR2 gene was appraised. The odds ratios (ORs) with 95% confidence intervals (CIs) under different genetic models were calculated. Results: A total of 13 studies were eligible in our meta-analysis according to the predefined inclusion and exclusion criteria. There was no significant association between asthma risk and rs5743708, rs3804099, and rs3804100 polymorphisms in TLR2 gene under any genetic model. With respect to the TLR2 rs4696480 polymorphism, significant association was detected between asthma susceptibility and TLR2 rs4696480 polymorphism under dominant model (OR = 2.455, 95% CI = 1.235–4.88, P  = .01) and codominant 3 model (OR = 2.776, 95% CI = 1.199–6.427,  = 0.017). Conclusions: Our meta-analysis reveals that the TLR2 rs4696480 polymorphism is significantly associated with asthma susceptibility, and the TLR2 rs4696480 polymorphism is a risk factor for asthma.